The amelioration of alcohol-induced liver and intestinal barrier injury by Lactobacillus rhamnosus Gorbach-Goldin (LGG) is dependent on Interleukin 22 (IL-22) expression. Issue 5 (2nd May 2022) - Ge, Yuli; Sun, Huiling; Xu, Lanman; Zhang, Weiping; Lv, Jiaojian; Chen, Yongping
ABSTRACT: Alcoholic liver disease (ALD) is a common clinical liver injury disease. Lactobacillus rhamnosus Gorbach-Goldin (LGG) has been revealed to alleviate alcohol-induced intestinal barrier and liver injury. However, the underlying mechanism of LGG treatment for ALD remains unclear. To clarify this aspect, a chronic plus binge ALD model was constructed using C57BL/6 mice in line with a chronic alcohol binge feeding protocol. Interleukin 22 (IL-22) level was determined by quantitative real-time polymerase-chain reaction and enzyme-linked immunosorbent assays. Effects of LGG in model or IL-22 knockdown in LGG-treated model on the liver injury and steatosis status, as well as intestinal barrier function were assessed by hematoxylin eosin (HE) staining. Levels of alanine aminotransferase (ALT), triglyceride (TG), and aspartate aminotransferase (AST) in serum were measured by the corresponding kit. Western blot analysis was conducted to detect protein expressions of intestinal tight junction protein 1 (ZO-1) and Claudin-1. Concretely, LGG elevated IL-22 level in liver tissues and serum, while inhibiting ALT, TG, and AST levels in alcohol-exposed mice. Moreover, LGG alleviated liver injury, steatosis, and intestinal barrier injury caused by alcohol, and enhanced ZO-1 and Claudin-1 expressions. Furthermore, IL-22 knockdown increased ALT, TG, and AST levels in serum, and aggravated liver injury, steatosis, and intestinal barrier injury. ZO-1 and Claudin-1 levels were downregulated by IL-22 silencing. Importantly, downregulation of IL-22 reversed the effect of LGG on the liver and intestinal barrier injury. To conclude, LGG protects against chronic alcohol-induced intestinal and liver injury via regulating the intestinal IL-22 signaling pathway. Graphical Abstract: uf0001